An IEC61850 communication model for network devices in smart substation - Feng DENG; Siyuan HE; Gaofeng ZHAO (Dianxin kexue)
An IEC61850 communication model for network devices in smart substation was proposed,and the network device status information management was imtroduced into a unified monitoring and management system of smart substation.The substation monitoring system can directly get the state information and configuration information of the communication network and network devices,such as link status,bandwidth status,port forwarding state,the port packet loss rate,bit error rate and so on.